Category Shift in the Translation of the Novel the Alchemist by Paulo Coelho - Syahputri, Diani; Wulan, Yuli (English Teaching and Linguistics Journal (ETLiJ), 2025)
This research investigates category shifts in the Indonesian translation of Paulo Coelho's novel